Any order is appropriate : it's all in equal measure : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Dowling, Deanna (Massey University, 2014)
Any order is appropriate; it’s all in equal measure. Multiple entry points, separating out the parts. Even by listing them I feel uncomfortable. This research enquiry takes the form of a number of different investigations over a period of two years, and within the scaffolding project there are a number of simultaneous explorations that have happened at once. It is for this reason that I have offered a document that aims to oppose a chronological order. This structure reflects how I consider each component in a project that contains objects, sites, place, people, and institutions. What has become apparent to me in this process is that the relationship between all these factors is more complex than I thought and warrants avoiding, or producing, a hierarchy. The task of translating a collection of art works from their separate periods of production has encouraged new outcomes in my own research and concerns that form around a system of interrelationships – raising questions such as what it means to be under construction or deconstruction, to be something in translation, in progress, in development? These thoughts have evolved from terms used to discuss thematic concerns in a number of my works and shift at times to a more abstract use of the words, notes and lists. I have made objects about construction in a city currently undergoing heavy urban modification.
Keywords: Art installations; Space (Art)